Are Knotted or Knotless Techniques Better for Reconstruction of Full-Thickness Tears of the Superior Portion of the Subscapularis Tendon? A Study in Cadavers. Issue 3 (8th March 2022) - Sgroi, Mirco; Kappe, Thomas; Ludwig, Marius; Fuchs, Michael; Dornacher, Daniel; Reichel, Heiko; Ignatius, Anita; Dürselen, Lutz; Seywald, Anne; Seitz, Andreas Martin
Abstract: Background: Knotted and knotless single-anchor reconstruction techniques are frequently performed to reconstruct full-thickness tears of the upper portion of subscapularis tendon. However, it is unclear whether one technique is superior to the other. Questions/purposes: (1) When comparing knotless and knotted single-anchor reconstruction techniques in full-thickness tears of the upper subscapularis tendon, is there a difference in stiffness under cyclic load? (2) Are there differences in cyclic gapping between knotless and knotted reconstructions? (3) Are there differences in the maximal stiffness, yield load, and ultimate load to failure? (4) What are the modes of failure of knotless and knotted reconstruction techniques? Methods: Eight matched pairs of human cadaveric shoulders were dissected, and a full-thickness tear of the subscapularis tendon (Grade 3 according to the Fox and Romeo classification) was created. The cadavers all were male specimens, with a median (range) age of 69 years (61 to 75). Before biomechanical evaluation, the specimens were randomized into two equal reconstruction groups: knotless single anchor and knotted single anchor. All surgical procedures were performed by a single orthopaedic surgeon who subspecializes in sports orthopedics and shoulder surgery. With a customized set up that was integrated in a dynamic material testing machine, the humeri were consecutively loaded from 10 N to 60 N, from 10 N to 100 N, and from 10 N to 180 N for 50 cycles. Furthermore, the gapping behavior of the tear was analyzed using a video tracking system. Finally, the stiffness, gapping, maximal stiffness, yield loads, and maximum failure loads of both reconstruction groups were statistically analyzed. Failure was defined as retearing of the reconstructed gap threshold due to rupture of the tendon and/or failure of the knots or anchors. After biomechanical testing, bone quality was measured at the footprint of the subscapularis using microCT in all specimens. Bone quality was equal between both groups. To detect a minimum 0.15-mm difference in gap formation between the two repair techniques (with a 5% level of significance; α = 0.05), eight matched pairs (n = 16 in total) were calculated as necessary to achieve a power of at least 90%. Results: The first study question can be answered as follows: for stiffness under cyclic load, there were no differences with the numbers available between the knotted and knotless groups at load stages of 10 N to 60 N (32.7 ± 3.5 N/mm versus 34.2 ± 5.6 N/mm, mean difference 1.5 N/mm [95% CI -6.43 to 3.33]; p = 0.55), 10 N to 100 N (45.0 ± 4.8 N/mm versus 45.2 ± 6.0 N/mm, mean difference 0.2 N/mm [95% CI -5.74 to 6.04]; p = 0.95), and 10 N to 180 N (58.2 ± 10.6 N/mm versus 55.2 ± 4.7 N/mm, mean difference 3 N/mm [95% CI -5.84 to 11.79]; p = 0.48). In relation to the second research question, the following results emerged: For cyclic gapping, there were no differences between the knotted and knotless groups at any load levels. The present study was able to show the following with regard to the third research question: Between knotted and knotless repairs, there were no differences in maximal load stiffness (45.3 ± 8.6 N/mm versus 43.5 ± 10.2 N/mm, mean difference 1.8 [95% CI -11.78 to 8.23]; p = 0.71), yield load (425.1 ± 251.4 N versus 379.0 ± 169.4 N, mean difference 46.1 [95% CI -276.02 to 183.72]; p = 0.67), and failure load (521.1 ± 266.2 N versus 475.8 ± 183.3 N, mean difference 45.3 [95% CI -290.42 to 199.79]; p = 0.69). Regarding the fourth question concerning the failure modes, in the knotted repairs, the anchor tore from the bone in 2 of 8, the suture tore from the tendon in 6 of 8, and no suture slipped from the eyelet; in the knotless repairs, the anchor tore from the bone in 2 of 8, the suture tore from the tendon in 3 of 8, and the threads slipped from the eyelet in 3 of 8. Conclusion: With the numbers available, we found no differences between single-anchor knotless and knotted reconstruction techniques used to repair full-thickness tears of the upper portion of subscapularis tendon. Clinical Relevance: The reconstruction techniques we analyzed showed no differences in terms of their primary stability and biomechanical properties at the time of initial repair and with the numbers available. In view of these experimental results, it would be useful to conduct a clinical study in the future to verify the translationality of the experimental data of the present study.